2021
DOI: 10.3991/ijim.v15i12.22503
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Factors Influencing Mobile Learning in Higher Education – A Systematic Review

Abstract: <p>In order to facilitate effective learning experiences for the students, mobile learning (m-learning) has evolved as a powerful component of education – learning and teaching. M-learning, as opposed to electronic learning (e-learning) which uses small and portable devices along with laptops and desktops, uses mostly small and portable technological tools. M-learning assists in imparting knowledge focusing on the need of the learner, accessibility, infrastructure, and interaction, irrespective of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
2
31
0
2
Order By: Relevance
“…In this paper, the authors’ approach was to discuss on innovation and benefits of information and communication technologies in education sector. It is also observed that, with the development of technologies, recent focus on how users (teachers and students) adapt such technologies will be continued (Gupta et al , 2021). Particularly, the analysis of student’s adoption towards technology use, parents’ perception towards online education and the wide scope of research dealing with the educational institutions using technology during unforeseen situation.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, the authors’ approach was to discuss on innovation and benefits of information and communication technologies in education sector. It is also observed that, with the development of technologies, recent focus on how users (teachers and students) adapt such technologies will be continued (Gupta et al , 2021). Particularly, the analysis of student’s adoption towards technology use, parents’ perception towards online education and the wide scope of research dealing with the educational institutions using technology during unforeseen situation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the research interest in how to develop, adopt and use mobile learning applications has also increased. Several researchers have started to investigate the main factors that promote and enhance the quality of mobile learning applications [43][44][45][46][47]. According to several studies in the information system context, identifying quality factors is a critical step for guaranteeing the successful implementation of any new system [48][49][50][51][52].…”
Section: Literature Review and Research Backgroundmentioning
confidence: 99%
“…No training for government Teachers (Kumar, 2020); (Hassan & Mirza, 2021); (Jagathkar & Jain, 2020); Students living in a remote village who are pursuing University degrees have no resources at home to attend E-learning classes (Kapasia, Paul, Roy, & Saha, 2020); Lack of infrastructure and lacking cross-platform collaboration (Paliwal, Singh, & Sharma, 2020) (Maity, Sahu, & Sen, 2021); (Daimary, 2020); (Mehta S. N., 2020); (Varekar, 2021); (Das D. , 2021) Lack of government reach to remote rural locations, lack of training government teachers, lack of outsourcing private elearning portals, infrastructure limitations, and socio-economic limitations (Jena, Impact of Covid-19 on higher education in India, 2020); (Bhavnani, Mukherjee, Bhopal, & Sharma, 2021); (Aparna, 2021); (Pramanick & Samaddar, 2021); (Gupta, Khan, & Agarwal, 2021); (Joshi & Dewangan, 2021); Lack of ICT acceptability for middle-aged teachers ; Middle school level students & teachers need more focus on using the e-learning application (Suneja & Bagai, 2021); Lack of Digital Library for future reference (Sivankalai, 2021); One directional research 1 Responses of Parents and Teachers are not covered (Yadav, Arora, Kumari, & Nandal, 2020) Non-Technical courses also needed to be included in E-Learning 2 Focused on professional and technical courses compared to nontechnical courses (Singh S. , 2020); The recommendation of courses varies from school curriculum (Lalitha & Sreeja, 2021) The communication gap between students and teacher 1…”
Section: Lack Of Resources 19mentioning
confidence: 99%
“…The study materials should be prepared to enable students to begin their studies in remote and rural places. The authors focus on tutors' perspectives on student isolation and what they suggest to do(Roy , 2021) Gupta et al (2021). researched Mobile learning that allows people to integrate learning in formal and casual situations.…”
mentioning
confidence: 99%
See 1 more Smart Citation